Know the effect of a program that was built on the strategy of the planning organizations in developing the grammatical skills of the Eighth grade students of basic education in Sana’a - Abdullah, Ahmed Ali (Journal of Curriculum and Teaching Methodology, 2023)
The goal of this study is to: Know the effect of a program that was built on the strategy of the planning organizations in developing the grammatical skills of the Eighth grade students of basic education in Sana’a. To achieve the goals of this study and to answer its questions, it was based on doing its procedures on ' The descriptive method ' to prepare the theoretical framework and quasi – experimental design. According to the related sources, papers and the dependable approach of the study, an achievement test has been done to know the effectiveness of the designed program on developing the grammatical skills. Also an experimental design of two groups was done (experimental- controller), the experiment have been applied on the study's samples represented in (60) students whom have been chosen intentionally and randomly from the students of 8th grade, the third cycle of basic education in Qutaibah Secondary school. The sample was divided into two groups equally. The experimental group (30) students, have been taught the grammatical skills using the computerized program designed according to the planning organizations strategy. And the controller group (30) students have been taught the grammatical skills using the usual way. After finishing the period of applying the experiment, the sample's data have been processed. The results were as follows: There are differences with statistical significance in the level of significance (0.05) between the levels of the students of the two groups in the post application of the grammatical skills that is based on the effect of the independent variable in favor of the experimental group. There are differences with statistical significance in the level of significance (0.05) between the levels of the students of the experimental group in the pre and post application of the grammatical skills that is based on the effect of the variable of time (pre - post) in favor of the post application. Recommendations: Reconsider and develop the curricula of the Arabic languages so that the planning organizations' strategy to make the learner an effective component is included. Design training programmes for Arabic teachers and train them in the use of systemic schemes in planning, implementing and evaluating the subject of Arabic in the third cycle of basic education.
Keywords: strategy; computer program; systematic Thinking; grammatical skills